2022
DOI: 10.1111/infa.12491
|View full text |Cite|
|
Sign up to set email alerts
|

Presence at a distance: Video chat supports intergenerational sensitivity and positive infant affect during COVID‐19

Abstract: COVID‐19 disrupted infant contact with people beyond the immediate family. Because grandparents faced higher COVID‐19 risks due to age, many used video chat instead of interacting with their infant grandchildren in person. We conducted a semi‐naturalistic, longitudinal study with 48 families, each of whom submitted a series of video chats and surveys, and most ( n = 40) also submitted a video of an in‐person interaction. Families were mostly highly‐educated, White/Caucasian, and lived be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…In addition, the use of video chat technologies can foster social benefits by helping maintain family connections with parents that are physically absent (McClure & Barr, 2017 ; McClure et al, 2015 ). Recent research taking place during the pandemic found that videochat allowed sensitive interactions between children and grandparents and favored child engagement and positive affect (Roche et al, 2022 ). Indeed, most health organizations deem this type of activity safe even in the early years.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of video chat technologies can foster social benefits by helping maintain family connections with parents that are physically absent (McClure & Barr, 2017 ; McClure et al, 2015 ). Recent research taking place during the pandemic found that videochat allowed sensitive interactions between children and grandparents and favored child engagement and positive affect (Roche et al, 2022 ). Indeed, most health organizations deem this type of activity safe even in the early years.…”
Section: Introductionmentioning
confidence: 99%
“…McClure et al [41] found that while grandmothers and families in general were remarkably flexible in engaging in joint visual attention with a young grandchild during video chat, there were individual differences: babies whose families were higher in frequency of joint visual attention behaviors showed increased attention. Individual differences in grandparent sensitivity also predicted infant valence [49,64].…”
Section: Limitationsmentioning
confidence: 92%
“…Developers and families may need to consider creative ways to include video social contingency. Strategies observed during intergenerational videochat interactions (e.g., Roche et al, 2022) and the emergence of services to facilitate eBook reading via video chat are two possible creative approaches. JME with people in the room also enhances learning (e.g., Dore et al, 2018; Zack & Barr, 2016) by tailoring to the individual needs of the child and making learning more meaningful.…”
Section: Immediate Applications: How To Enhance Learning From Mediamentioning
confidence: 99%